Impact of the MDM2 SNP309 and p53 Arg72Pro polymorphism on age of tumour onset in Li-Fraumeni syndrome. Issue 6 (28th October 2005) - Bougeard, G; Baert-Desurmont, S; Tournier, I; Vasseur, S; Martin, C; Brugieres, L; Chompret, A; Bressac-de Paillerets, B; Stoppa-Lyonnet, D; Bonaiti-Pellie, C; Frebourg, T
Abstract : Li-Fraumeni syndrome, resulting from p53 ( TP53 ) germline mutations, represents one of the most devastating genetic predispositions to cancer. Recently, the MDM2 SNP309 (T→G variation) was shown to be associated with accelerated tumour formation in p53 mutation carriers. The impact of the common p53 codon 72 polymorphism on cancer risk remains controversial. We therefore investigated the effect of these two polymorphisms in 61 French carriers of the p53 germline mutation. The mean age of tumour onset in MDMD2 SNP309 G allele carriers (19.6 years) was significantly different from that observed in patients homozygous for the T allele (29.9 years, p<0.05). For the p53 codon 72 polymorphism, the mean age of tumour onset in Arg allele carriers (21.8 years) was also different from that of Pro/Pro patients (34.4 years, p<0.05). We observed a cumulative effect of both polymorphisms because the mean ages of tumour onset in carriers of the MDM2 G and p53 Arg alleles (16.9 years) and those with the MDM2 T / T and p53 Pro/Pro genotypes (43 years) were clearly different (p<0.02). Therefore, our results confirm the impact of the MDM2 SNP309 G allele on the age of tumour onset in germline p53 mutation carriers, and suggest that this effect may be amplified by the p53 72 Arg allele. Polymorphisms affecting p53 degradation therefore represent one of the rare examples of modifier genetic factors identified to date in mendelian predispositions to cancer.